Geochemically induced shear slip in artificially fractured dolomite- and clay-cemented sandstone. (October 2021) - Fuchs, Samantha J.; Crandall, Dustin; Moore, Johnathan E.; Sivaguru, Mayandi; Fouke, Bruce W.; Espinoza, D. Nicolas; Akono, Ange-Therese; Werth, Charles J.
Highlights: Sandstone fractures were exposed to acidic or reservoir-simulated brine flow Acidic brine flow induced greater shear slip than reservoir conditions Acidic brine dissolved cementing dolomite, reducing fracture toughness Fracture surface roughness and porosity increased with carbonate dissolution Abstract: Geologic carbon sequestration in deep saline aquifers results in a low pH brine plume that pushes into subsurface storage reservoirs and can access pre-existing or induced microfractures. This work investigates the effect of acidic brine on displacement of an artificial fracture under stress in the dolomite- and clay-cemented Bandera Gray sandstone. Samples were held under stress in a custom flow cell housed within an industrial CT scanner, and either acidic (pH 4) or reservoir-simulated (pH 8.3) brine was flowed through the artificial fracture for seven days. CT imaging shows that acidic brine resulted in greater shear slip than reservoir-simulated brine, with 0.379 ± 0.022 mm shear slip after pH 4 flow and only 0.213 ± 0.011 mm slip after pH 8.3 flow. Fracture surfaces exposed to acidic brine had rougher surfaces and lower fracture toughness, respectively, than those exposed to reservoir-simulated brine. SEM images of fracture surfaces indicate a loss by area of Fe-dolomite cementing crystals (6.05 ± 1.37% to 3.78 ± 0.73%) after exposure with the acidic brine, as well as a corresponding porosity increase (24.6 ± 1.1% to 26.1 ± 1.1%). These results indicate dissolution and weakening of the dolomite cements by acidic brine frees individual grains at the fracture surface to move, resulting in geochemically-induced stress release. Acidic brine created from geological carbon sequestration can dissolve sandstone cements and lead to increased shear slip at fracture interfaces, but further work at larger scales and with more realistic fracture conditions is needed.